2014
DOI: 10.1080/03079457.2014.940496
|View full text |Cite
|
Sign up to set email alerts
|

The role of avian reoviruses in turkey tenosynovitis/arthritis

Abstract: Turkey arthritis reovirus (TARV) has been isolated from the gastrocnemius tendons and tibiotarsal joint fluid of lame male turkeys >12 weeks old in the Midwest. Two experiments were conducted to compare the pathogenicity in turkeys of three TARVs (TARV-MN2, TARV-MN4 and TARV-O'Neil), one turkey enteric reovirus (TERV strain MN1) and one chicken arthritis reovirus (CARV strain MN1). Two hundred microlitres of virus were inoculated by the oral, intratracheal, or footpad route into 6-day-old poults placed in isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
(27 reference statements)
1
18
0
2
Order By: Relevance
“…The M2-III genotype contained TARV-MN4, TERV-MN5, an enteric CRV strain (AVS-B) isolated in 2006, and an arthritis CRV strain (916S1) isolated in 1992 from Taiwan further indicating possibility of reassortment between chicken and turkey reoviruses. Experimentally, TARVs and TERVs are able to replicate in chickens and may be able to cause enteritis/diarrhea while CRVs are able to replicate in turkeys without causing any disease (Rosenberger et al, 2013a;Sharafeldin et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The M2-III genotype contained TARV-MN4, TERV-MN5, an enteric CRV strain (AVS-B) isolated in 2006, and an arthritis CRV strain (916S1) isolated in 1992 from Taiwan further indicating possibility of reassortment between chicken and turkey reoviruses. Experimentally, TARVs and TERVs are able to replicate in chickens and may be able to cause enteritis/diarrhea while CRVs are able to replicate in turkeys without causing any disease (Rosenberger et al, 2013a;Sharafeldin et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…From tendons and/or joint fluids of these cases, we isolated TARVs in QT-35 cells as previously described (Mor et al, 2013b). For histopathology, gastrocnemius and digital flexor tendons were removed and immersed in 10% buffered formalin and processed as previously described (Sharafeldin et al, 2014). Fecal samples from enteritic turkeys were also processed for isolation of TERVs as previously described (Jindal et al, 2010;Mor et al, 2013a).…”
Section: Sample Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…We have found that inoculation of 1-week-old turkey poults with TARV induces histologic tenosynovitis at 4 weeks PI without clinical lameness [5]. However, clinical lameness can be seen at 8 weeks PI, which later progresses at 12 and 16 weeks PI [6].…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions were absent in poults inoculated either with turkey enteric reovirus (TERV) or with chicken arthritis reovirus (CARV) [5]. Oral inoculation of TARV in 1-week-old turkey poults induced clinical signs of lameness at 8 weeks of age, which increased in severity by 12 and 16 weeks of age [6].…”
Section: Introductionmentioning
confidence: 99%